THE COMMON MISTAKES OF UNDERGRADUATE EFL STUDENTS IN WRITING ARGUMENTATIVE ESSAYS - Suhartoyo, Eko; Ni’mah, Dzurriyyatun; Ismiatun, Febti (Universitas Negeri Semarang, 2020)
The argumentative essay seems to be challenging for university students (Ka-kan-dee & Kaur, 2015), including in Indonesia. Despite its prominence, this writing genre needs complex thoughts in the process of text making. As an impact, these troubles create hinders so that students show the poor quality in developing the essay. This issue motivated a study that aimed at highlighting the students’ mistakes in writing an argumentative essay through a mixed-method approach. The participants were chosen disorderly from university students majoring in English education and engaged in filling out the questionnaires and interviews sequentially. The explanation data analysis was then applied by means of construing the common problems coped with the participants quantitatively as well as qualitative analysis. The results of the analysis remarked that participants encountered numerous complexities in building the argumentative essay, especially low achievers. They revealed that the features of introduction, conclusion, and grammar were so stressful and high demanding to write so they required effective strategies as well as writing digital tools to resolve the challenges. Foreclosing, the last part of this study provides meaningful insight regarding the curricula of teaching argumentative essays, such as materials and instructions.